Placental Insertion into the Cervix with Cervical Shortening as a Clinical Sign to Suspect Cervico-Isthmic Pregnancy: A Case Report and Literature Review - Chisa Ito; Hirotada Suzuki; Yusuke Amano; Shigeyoshi Kijima; Akihide Ohkuchi; Hironori Takahashi; Hiroyuki Fujiwara (Case Reports in Obstetrics and Gynecology)
The clinical signs of cervico-isthmic pregnancy during pregnancy remain unknown. We herein report a case of cervico-isthmic pregnancy showing placental insertion into the cervix with cervical shortening, with a final diagnosis of placenta increta at the uterine body and cervix. A 33-year-old multiparous woman with a history of cesarean section was referred to our hospital at 7 weeks of gestation with suspected cesarean scar pregnancy. Cervical shortening with a cervical length of 14 mm was noted at 13 weeks of gestation. The placenta is gradually inserted into the cervix. An ultrasonographic examination and magnetic resonance imaging strongly suggested placenta accreta. We planned elective cesarean hysterectomy at 34 weeks of gestation. The pathological diagnosis was cervico-isthmic pregnancy with placenta increta at the uterine body and cervix. In conclusion, placental insertion into the cervix with cervical shortening in the early pregnancy period may be a clinical sign to suspect cervico-isthmic pregnancy.